Proceedings of the Third Workshop on Economics and Natural Language Processing 2021
DOI: 10.18653/v1/2021.econlp-1.4
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Bankruptcy Prediction with Domain-Adapted BERT

Abstract: This study performs BERT-based analysis, which is a representative contextualized language model, on corporate disclosure data to predict impending bankruptcies. Prior literature on bankruptcy prediction mainly focuses on developing more sophisticated prediction methodologies with financial variables. However, in our study, we focus on improving the quality of input dataset. Specifically, we employ BERT model to perform sentiment analysis on MD&A disclosures. We show that BERT outperforms dictionary-based pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…They showed that the method ranks relevant news highly and positively correlated with the accuracy of the initial stock price prediction task. Kim and Yoon ( 2021 ) proposed a model to predict impending bankruptcies using BERT. They showed that BERT outperforms dictionary-based predictions and Word2Vec-based predictions.…”
Section: Related Studymentioning
confidence: 99%
“…They showed that the method ranks relevant news highly and positively correlated with the accuracy of the initial stock price prediction task. Kim and Yoon ( 2021 ) proposed a model to predict impending bankruptcies using BERT. They showed that BERT outperforms dictionary-based predictions and Word2Vec-based predictions.…”
Section: Related Studymentioning
confidence: 99%
“…(A. G. Kim & Yoon, 2021) The concepts of bankruptcy and credit checks have been established for a significant duration. During the 1890s, a prominent method of probability computation emerged, which presented compelling evidence.…”
Section: Introductionmentioning
confidence: 99%